Odpowiedzi

2009-11-17T18:19:21+01:00
(1,2)+(-0,008)= 1,2 - 0,008 = 1,192
(-16,8)+(+20.1) = 3,3
(-0.999)+(1.001)= 0,002
(-144)+466 = 322
538+(-274) = 538 - 274 = 264
(-275)+538 = 263
(-333)+(-666) = -333 - 666 = -999
(-666)+(-338) = - 666 - 338 = - 1004
(-5.8)+(4.9)+(-7,2) = -5,8 +4,9 -7,2 = -8,1
(-5.9)+4,9+(-7.3) = -5,9 + 4,9 - 7,3 = -8,3
(-36)+(-0.25)+(-0.1) = - 36 - 0,25 - 0,1 = -36,35
(-36)+(-0.2)+(-0.25) = - 36 - 0,2 - 0,25 = - 36,45

;)
1 5 1
2009-11-17T18:24:12+01:00
(1.2)+(-0.008)=1.192
-16.8+20.3=3.5
-0.999+1.001=2
-144+466=322
538+(-274)=264
-275+538=263
-666+(-338)=-1004
-5.8+4.9+(-7.2)=-8.1
-5.9+4.9+(-7.3)=-8.3
-36+(-0.25)+(-0.1)=-36.35
-36+(-0.25)+(-0.2)=36.45
1 1 1